International goals to promote patient safety in intra-hospital transport: integrative review (Research, Society and Development, 2022)
Introduction: Errors and complications resulting from health care that cause harm to patients are called adverse events (AE), which can be preventable and constitute a great challenge for the nursing team, as they compromise the quality of health care and the patient safety in intra-hospital transport (IHT). Objective: The objective of this study is to present an integrative review about the contribution of nursing care to patient safety in the hospital environment, as well as the 6 international goals to be met for the success of their actions. Materials and methods: Data collection took place between 2017 and 2022, through the following databases: Scientific Electronic Library Online (SCIELO), Google Scholar, and LILACS - Bireme (Latin American and Caribbean Literature in Health Sciences). Results: Through the search carried out from the databases described, a total of 65 articles were found from the descriptors and search criteria applied to the research. Subsequently, the titles and abstracts were read, where 12 studies were selected that presented themselves according to the research theme. Discussion: After selecting the articles, we observed that although there are many studies related to patient safety, few address in-hospital transport (IHT). Conclusion: We emphasize the importance of the nursing team, reinforcing the need for professional qualification, for decision making in the institution's strategy, based on evidence on the importance of management, in order to adopt measures for patient safety.